Intra-Articular Injection of Adipose-Derived Stromal Vascular Fraction in Osteoarthritic Temporomandibular Joints: Study Design of a Randomized Controlled Clinical Trial - Schipper, Jan Aart M.; Tuin, Aartje Jorien; van Dongen, Joris A.; van Bakelen, Nico B.; Harmsen, Martin Conrad; Spijkervet, Fred K. L. (Bioengineering (Basel), 2024)
Introduction: Temporomandibular joint (TMJ) osteoarthritis is a degenerative disease of the TMJ. It is characterized by progressive degradation of the extracellular matrix components of articular cartilage, with secondary inflammatory components leading to pain in the temporomandibular region and reduced mouth opening. Current treatments do not halt disease progression, hence the need for new therapies to reduce inflammation and, consequently, improve symptoms. The aim of our randomized controlled clinical trial protocol is to investigate the efficacy of adjuvant intra-articular injections of autologous tissue-like stromal vascular fraction (tSVF), compared to arthrocentesis alone, in reducing pain and improving mouth opening in TMJ osteoarthritis patients. Materials and Methods: The primary endpoint analysis will consist of the visual analogue scale (VAS) for pain. The secondary endpoint analyses will include maximal interincisal mouth opening measurements; assessment of oral health and mandibular function based on the oral health impact profile (OHIP) questionnaire and mandibular functional impairment questionnaire (MFIQ); complications during the follow up; synovial cytokine analysis at baseline and after 26 weeks; and nucleated cells and tSVF (immuno)histochemistry analyses of the intervention group. Discussion: Our randomized clinical trial protocol will be applied to evaluate the efficacy of a new promising tSVF injection therapy for TMJ osteoarthritis. The safety of intra-articular injections of tSVF has been proven for knee osteoarthritis. However, since a tSVF injection is considered a heterologous application of cell therapy, the regulatory requirements are strict, which makes medical ethical approval challenging.